2016
DOI: 10.1016/j.joca.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Synovial changes detected by ultrasound in people with knee osteoarthritis – a meta-analysis of observational studies

Abstract: SummaryObjectivesTo examine the prevalence of synovial effusion, synovial hypertrophy and positive Doppler signal (DS) detected by ultrasound (US) in people with knee osteoarthritis (OA) and/or knee pain compared to that in the general population.MethodA systematic literature search was undertaken in Medline, EMBASE, Allied and Complementary Medicine, PubMed Web of Science, and SCOPUS databases in May 2015. Frequencies of US abnormalities in people with knee OA/pain, in the general population or asymptomatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…The association between synovial changes and KP in OA have been investigated previously. In our recent meta-analysis [ 42 ], seven out of 10 studies reported a positive association between KP and effusion and two out of six studies reported an association with synovial hypertrophy. However, most studies did not adjust for ROA.…”
Section: Discussionmentioning
confidence: 99%
“…The association between synovial changes and KP in OA have been investigated previously. In our recent meta-analysis [ 42 ], seven out of 10 studies reported a positive association between KP and effusion and two out of six studies reported an association with synovial hypertrophy. However, most studies did not adjust for ROA.…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasound cannot assess cartilage deep in the joint or intra-bone lesions, it is well suited to assess inflammatory changes. A large meta-analysis of ultrasound-detected synovial changes found that people with knee OA or knee pain had high prevalence of effusion, synovial hypertrophy and power Doppler signals (ranging from 33 to 52% of the knees), and that these measures correlated well with histological findings [ 27 ]. A large multicentre study using ultrasound in 600 people with symptomatic knee OA demonstrated synovial inflammation or effusion in 46% of the population, despite using a strict definition of synovial hypertrophy [ 28 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…US detection of synovial effusion and synovial hypertrophy in knees is more sensitive than clinical examination 9 , 10 , correlates well with histological findings 11 , 12 and correlates well with MRI in visualising effusion 13 , 14 . However, evidence regarding “normal” values for effusion and hypertrophy in the general population is limited 15 . For example, the only study to provide reference values for effusion was based on a group of healthy volunteers aged 20–60 years old ( n = 102) 16 , which is a low age range for OA, and no population studies have reported normal values for synovial hypertrophy or prevalence of Power Doppler signal (PDS).…”
Section: Introductionmentioning
confidence: 99%